Fossil fuel to the fire: Energy and inflation in Europe - Max Krahé; Felix Heilmann (Dezernat Zukunft e.V., 2023)
Energy made an outsized contribution to the recent inflationary wave in Europe: On average, 50 percent of year-on-year inflation in 2022 was directly due to energy, the vast majority of which was due to fossil fuel price rises. Additional inflationary effects followed from indirect impacts on other prices, especially food. Renewable energy can help fight inflation both in the short and in the long run. In the short run, faster renewable energy deployment saved European consumers around 95 billion euro between 2021 and 2023 and reduced electricity prices by up to 15 percent (IEA 2023c). In the long run, the secular downwards trend in renewable energy costs suggests further cost saving potential and, once the transition is complete, price stability. The situation is more complicated in the mid-transition. Three challenges appear salient: As long as electricity prices remain linked to fossil fuel prices, especially gas, any increase in fossil fuel price volatility spills over into the pricing of electricity. Supply chain risks may materialize as renewable energy deployment accelerates. And if investment in grids, energy storage, and supply- and demand-side flexibility fails to keep up with accelerating renewable deployment, further bottlenecks and price spikes may emerge. However, these risks are not set in stone. The extent to which they will materialize will depend on today's policy choices. While further research and policy action is needed on the mid-transition, the overall picture that emerges from our analysis is therefore clear: fossil fuels added to the economic and political instability of recent years. Replacing them with renewables can become a pillar of future stability.
Keywords: 330; Inflation; FossilFuels; RenewableEnergy; Europe